2013
DOI: 10.3857/roj.2013.31.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Role of salvage radiotherapy for regional lymph node recurrence after radical surgery in advanced gastric cancer

Abstract: PurposeTo evaluate the role of salvage radiotherapy (RT) for the treatment of regional lymph node recurrence (RLNR) after radical surgery in advanced gastric cancer.Materials and MethodsWe retrospectively analyzed medical records of 26 patients who underwent salvage treatment after diagnosis of RLNR between 2006 and 2011. Patients with peritoneal seeding or distant metastasis were excluded. Eighteen patients received RT with or without chemotherapy and the other 8 did chemotherapy only without RT. A three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Like other carcinomas, GC is featured by infinite cell proliferation and tumor growth, which is attributed to the promotive influences of oncogenic regulators and the inhibitory influences of tumor-suppressive regulators [4][5][6]. In the current time, the main treatment methods for GC patients are surgical operation, chemotherapy and radiotherapy [7,8]. Considering the low diagnosis rate and high recurrence rate of GC, it is imperative to investigate more GC therapeutic targets to fight against the serious disease for human beings.…”
Section: Introductionmentioning
confidence: 99%
“…Like other carcinomas, GC is featured by infinite cell proliferation and tumor growth, which is attributed to the promotive influences of oncogenic regulators and the inhibitory influences of tumor-suppressive regulators [4][5][6]. In the current time, the main treatment methods for GC patients are surgical operation, chemotherapy and radiotherapy [7,8]. Considering the low diagnosis rate and high recurrence rate of GC, it is imperative to investigate more GC therapeutic targets to fight against the serious disease for human beings.…”
Section: Introductionmentioning
confidence: 99%
“…For local advanced gastric cancer, since tumors are located in the stomach, in which regional lymph nodes and distant metastasis have not yet occurred, the majority of literatures reported that systemic chemotherapy combined with radiotherapy of gastric lesions and regional lymph nodes could improve its effective rate and survival time. [ 2 , 3 ] For gastric cancer with lymph node metastasis, a retrospective study in South Korea revealed that [ 19 ] the survival time of patients with gastric cancer with lymph node recurrence in the abdominal cavity after an operation, who underwent radiotherapy of recurrent lymph nodes, was significantly longer than patients who did not undergo radiotherapy (36 vs 16 months, P < .001). Sun et al [ 20 ] retrospectively analyzed 79 patients with celiac lymph node metastasis after D2 radical resection of gastric cancer, where patients received external radiotherapy on the basis of systemic chemotherapy or supportive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that RT to regional LN recurrence from gastric cancer lowered local recurrence. [27] The liver is one of the common sites of distant metastasis of gastric cancer, chemotherapy has been considered as the standard treatment. However, a single institution phase I-II study for primary and metastatic liver tumors achieved a 2-year local control of 86% and 2-year overall survival rates of 62% with SBRT, [28] which indicated RT was an effective treatment for patients with Oligometastatic in liver.…”
Section: Discussionmentioning
confidence: 99%